**2 * s + s + 12 = 132**, friend cando this making use of the following steps:

**2 * s + s + 12 =132**3 * s =132 - 123 * s =120 /3s = 120/3

**s = 40**Thecorrect an outcome would be

**A. S = 40**.

You are watching: Solve this equation: 2s + s + 12 = 132.

2s+ s+ 12= 132⇒ (2s+ s)+ 12= 132 (combine prefer terms)⇒ 3s+ 12= 132⇒ 3s= 132 -12 (inverse operation)⇒ 3s= 120⇒ s= 120/3⇒ s= 40Final ptcouncil.net:

**A. S= 40**.

**ptcouncil.net:**

y

=

3

2

x

Rewrite in slope-intercept form.

Tap for an ext steps...

y

=

3

2

x

Use the slope-intercept form to find the slope and y-intercept.

Tap for an ext steps...

Slope:

3

2

y-intercept:

(

0

,

0

)

Any line have the right to be graphed using two points. Choose two

x

values, and plug them right into the equation to find the equivalent

y

values.

Tap for much more steps...

See more: Should Video Game Titles Be Italicized ? Should The Title Of A Board Game Be Italicized

x

y

0

0

2

3

Graph the line making use of the slope and the y-intercept, or the points.

Slope:

3

2

y-intercept:

(

0

,

0

)

x

y

0

0

2

3

image of graph

**Step-by-step explanation:**

**Step-by-step explanation:**

As, castle all space consecutive and also odd

The equation = x + (x + 2) + (x + 4) = 39

X represent the first number and likewise the the smallest one

X + 2 is the 2nd number, it"s consecutive and odd so we need to add 2

X + 4 is the 3rd number, it"s consecutive and also odd to (x+2) therefore we will certainly just add 2 an ext = x + 2 +2 = x +4

So x + (x + 2) + (x + 4) = 39

3x + 6 = 39

3x = 39 - 6

3x = 33

x = 11

So smallest number = 11

And x + 2 = 11+2 = 13 (second number)

And x + 4 = 11 + 4 = 15 ( 3rd number )

So only since u asked for the the smallest

So it"s 11

5 0

3 month ago

Solve making use of the quadratic formula.q2 + 69 + 9 = 0

Tasptcouncil.net <4>

**ptcouncil.net:**

**the value of q = -3**

**Step-by-step explanation:**

The computation of the equation is displayed below:

Given that

q^2 + 6q + 9 = 0

q^2 + 3q+ 3q + 9

q(q + 3) + 3(q + 3)

(q+3) (q+3)

q = -3

Hence, after fixing it **the value of q = -3**

4 0

1 month ago

Jenna constructs the design to represent 3 x 2 + 11 x - 4 what determinants does Jenna need to version for the sides

Sveta_85 <38>

We have thaty=3x²+11x-4using a graph tool---------> to find the roots of the equationsee the attached figurethe solution isx=-4x=0.333----> 1/3so (x+4)=0and(x-1/3)=0---------> (3x-1)/3=0-------> (3x-1)=0(x+4)*(3x-1)

**the ptcouncil.net is**

**(3x-1) and (x+4)**

6 0

11 month ago

Other questions:

×

Add ptcouncil.net

Send

×

Login

E-mail

Password

psychic me

Login

no registered? rapid signup

×

Signup

Your nickname

E-mail

Password

Signup

close

Login Signup

asking question!